PENGARUH PELAYANAN INTERNAL TERHADAP LOYALITAS KERJA PEGAWAI DI KANTOR KECAMATAN BATULAPPA - Imam, Imam; Kadir, Abdul (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aimed to examine the effect of internal services on employee job loyalty in the Kantor Camat Batulappa, Kabupaten Pinrang. This research uses quantitative research methods. The sample used was 22 samples. Testing instruments with validity and reliability tests. Methods of data analysis using statistical tools using SPSS (Statistical Package for Social Science) software version 22. The results of data analysis indicate that there is a positive influence between internal services on employee job loyalty. That is indicated by the magnitude of the t-count value that is greater than the t-table (25,600> 2,086). the results of simple linear regression get the equation y = 1.615 + 0.514X. So that it has a positive relationship between internal service and job loyalty of employees at the Kantor Camat Batulappa, Kabupaten Pinrang.